Has the Paycheck Protection Program succeeded? - R. Glenn Hubbard; Michael R. Strain (American Enterprise Institute (AEI), 2020)
Enacted March 27, 2020, the Paycheck Protection Program (PPP) was the most ambitious and creative fiscal policy response to the Pandemic Recession in the United States.
Keywords: A; 330; Paycheck Protection Program; PPP; Pandemic Recession; CARES Act; COVID-19